Determinan Kemiskinan Anak di Sulawesi, Maluku dan Papua (Studi Kasus Perspektif Kesehatan) - Mootinelo, Satria; Abdul, S.E., M.Si, Dr. Irawati; Akib, S.E., M.E., Fitri Hadi Yulia (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2025)
This study aims to analyze health-related factors that contribute to the likelihood of children experiencing poverty in Sulawesi, Maluku, and Papua. The data used in this study are derived from the SUSENAS (Survei Sosial Ekonomi Nasional of National Socio-Economic Survey) in March 2023 and are analyzed using a logistic regression method. The logistic model is used to determine the probability of a child experiencing poverty due to several health-related factors, including health complaints in the past month, health insurance ownership, breastfeeding, smoking experience, child disability status, and household head disability status. Among the total child respondents observed, 23 18% live below the poverty line, while 76.82% live above it. A child is categorized as poor if they live in a household with per capita expenditure below the national poverty line as of March 2023, IDR 550,458 per capita per month The findings also show that breastfeeding and household head disability status significantly contribute to a higher likelihood of children experiencing poverty in Sulawesi, Maluku, and Papua Conversely, recent health complaints and health insurance ownership significantly contribute to a lower likelihood of children falling into poverty Meanwhile, smoking experience and child disability status show a negative correlation with poverty but do not significantly affect the likelihood of a child experiencing poverty in the regions studied